Human milk : composition, clinical benefits and future opportunities - Allen, Lindsay Helen 1946-; Bode, Lars; Donovan, Sharon Marie; Donovan, Sharon Marie; German, J. Bruce; German, J. Bruce; Haschke, Ferdinand 1948-; Lönnerdal, Bo 1938-; Lucas, Alan (Nestlé Nutrition Institute workshop series, 2019)
Human milk contains all of the essential nutrients and other functional components thought to have short- and long-term neonatal health benefits, such as positive biological effects on growth, metabolism, cognition, and immunity. This publication brings together the world's experts who touch on the spectrum of current knowledge, from the history and mechanics of breastfeeding, its physiological and clinical effects, to the new surprises revealed by metabolomics and comparative biology. One of the key points made is that human milk is not only a source of essential nutrients, but also contains a variety of bioactive substances. These include essential microbes, long-chain fatty acids, complex oligosaccharides, nucleotides, and bioactive signaling proteins and hormones. This book provides clinicians and researchers with useful insights from multiple perspectives on the various aspects of human milk and lactation.